(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In both ancient Eastern medicine and modern Western physiology, sleep is recognized not as a passive state of rest, but as an active, vital process of biological restoration. Ayurveda categorizes Nidra (sleep) as one of the Trayopastambha (the three pillars of life, alongside food and controlled sensory or sexual energy). When the biological urge to sleep arises, it is termed a Vega (a natural, impending bodily reflex). Forcible suppression of this urge is called Nidra Vega Dharana (or Nidra Vega Vidharana). This review explores the systemic causes, multi-organ consequences, and integrative preventive measures of suppressing the sleep urge from both Ayurvedic and modern clinical perspectives.